The Effect of Audio Therapy Using Qur'an Recitation on Stress Reduction in Elderly People at the Harapan Kita Social Welfare Institution for the Elderly in Palembang - Afdallah, Afdallah; Putra, Riko Sandra (INDOGENIUS, 2026)
Background & Objective: An elderly person is someone who has reached the age of 60 or above. The WHO classifies the elderly into four categories: middle age between 45 and 59 years old, elderly between 60 and 74 years old, old between 75 and 90 years old, and very old above 90 years old. Living arrangements can cause stress for the elderly, as is the case for those in nursing homes. This study aims to determine the effect of audio therapy using recitations from the Qur'an on reducing stress levels among the elderly at the Harapan Kita Social Welfare Home for the Elderly in Palembang. Method: This study used a pre-experimental design with a one-group pre-post-test design. In this study, the sample was given a pretest (initial observation) before the intervention, followed by the intervention, and then a posttest (final observation). The population in this study was all elderly people at the Harapan Kita Palembang Social Welfare Home for the Elderly in 2024, with a sample size of 35 respondents. Sampling was conducted using purposive sampling. Result: The results of the study showed that there was an effect of audio murottal Qur'an therapy on reducing stress levels in the elderly (p.value = 0.001). Conclusion: Audio murottal Qur'an therapy is effective in reducing stress levels in the elderly. It is hoped that this therapy can be applied as a non-pharmacological intervention in social institutions and nursing services.